Expressions of NeuroD and GAP43 as diagnostic markers for olfactory neuroblastoma - Furukawa, Tatsuya; Tatehara, Shun; Teshima, Masanori; Shinomiya, Hirotaka; Inokuchi, Go; Komatsu, Masato; Hara, Shigeo; Zen, Yoh; Nibu, Ken-ichi (Auris, nasus, larynx, 2023)
Olfactory neuroblastoma (ONB) is often difficult to pathologically distinguish from other small round cell tumors (SRCTs) arising in the nasal cavities. Although there are several diagnostic markers used for differential diagnosis of ONB, these molecules are also expressed in various neuronal derived tumors. Here, we examined the expression of NeuroD, GAP43, and olfactory marker protein (OMP) in ONB and non-ONB SRCT to determine their utility in the differential diagnosis of ONB. Twenty-six patients diagnosed with and treated for ONB at Kobe University Hospital between 1997 and 2017 with formalin-fixed, paraffin-embedded biopsy or surgical resection specimens were included. The expressions of NeuroD, GAP43, and OMP were immunohistochemically examined in these 26 ONB specimens and specimens from 13 SRCTs arising in the nasal cavities for reference. Among the 26 ONB samples, focal, patchy, and marked staining for NeuroD was observed in 4, 3, and 9 samples, respectively. Focal, patchy, and marked GAP43 staining was observed in 5, 3, and 11 samples, respectively. Consequently, marked positive staining for either NeuroD or GAP43 was observed in 54% (14/26) of ONBs. Among the 13 SRCTs, marked staining for NeuroD was observed in two small cell carcinomas, one undifferentiated carcinoma, and one neuroendocrine carcinoma, whereas marked positive staining for GAP43 was observed only in one undifferentiated carcinoma. No specimen in this study exhibited OMP staining. Our results suggest possible roles of GAP43 immunostaining in the differential diagnosis of ONB.